2016
DOI: 10.2527/jas.2015-0111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different alfalfa hay levels on growth performance, rumen fermentation, and structural growth of Holstein dairy calves1

Abstract: Introducing forage in dairy calf diets during the preweaning period stimulates development of rumen capacity and function and gut wall integrity. It was hypothesized that calves fed alfalfa hay (AH) at greater levels (up to 25% of DM) would result in an increase in starter diet intake and growth performance. The objective of this study was to determine the effects of increasing levels of supplemental AH on growth performance, rumen fermentation, blood metabolites, and feeding behavior in intact male dairy calv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
43
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 30 publications
14
43
2
4
Order By: Relevance
“…Most of the studies (21 studies, accounting for 84% of summarized studies) explored in this review showed a positive effect of forage inclusion on rumen fluid pH in dairy calves, while very few reported no difference (four studies, accounting for 16% of summarized studies) or negative impact (Table 7). In agreement with a previous meta-analysis, our literature search showed that forage could improve the rumen fluid pH when supplemented to calves, though it might be dependent on the forage source [38,40]. Alfalfa hay is more likely to modulate rumen fluid pH during the milk-feeding period than other types of forages [33].…”
Section: Rumen Fluid Ph and Fermentationsupporting
confidence: 90%
See 3 more Smart Citations
“…Most of the studies (21 studies, accounting for 84% of summarized studies) explored in this review showed a positive effect of forage inclusion on rumen fluid pH in dairy calves, while very few reported no difference (four studies, accounting for 16% of summarized studies) or negative impact (Table 7). In agreement with a previous meta-analysis, our literature search showed that forage could improve the rumen fluid pH when supplemented to calves, though it might be dependent on the forage source [38,40]. Alfalfa hay is more likely to modulate rumen fluid pH during the milk-feeding period than other types of forages [33].…”
Section: Rumen Fluid Ph and Fermentationsupporting
confidence: 90%
“…In the early 2000s, several studies began to investigate the effect of lower levels of forage inclusion in the diet on pre-weaned calf performance. Most of them included a proportion of forage ranging between 5 and 25% of total solid feed intake [15,19,22,27,[37][38][39][40]. In contrast to previous studies, most studies either reported an increase [19,22,38,40] or a lack of differences [27,37] in DMI, ADG, and BW, indicative of multifactorial effects in these studies.…”
Section: Forage Factorsmentioning
confidence: 92%
See 2 more Smart Citations
“…The total VFA concentrations were unaffected among the groups, which might be the result of the same ratio of forage to concentration of treatment diets 36 , or might be caused by the fact that the output of total VFA was equivalent to the amount of absorption in the rumen among all treatments 37 . In the present research, the observed concentrations of acetate and propionate, and the acetate to propionate ratio were not significantly different, probably because of the similar ruminal pH values caused by the dietary-associated shifts 38 .…”
Section: Discussioncontrasting
confidence: 48%